2007
DOI: 10.1037/0096-1523.33.4.845
|View full text |Cite
|
Sign up to set email alerts
|

Judging and actualizing intrapersonal and interpersonal affordances.

Abstract: The current study investigated the perception of intrapersonal, interpersonal, and tool-based grasping possibilities. In Experiment 1, participants judged whether they would grasp planks of wood-presented in ascending, descending, and random orders of length-using one hand (1H), two hands (2H), or with a tool that extended their reach (TH). In Experiment 2, participants physically grasped the planks using 1H, 2H, or TH. In Experiments 3 and 4, the choice of TH was replaced with a choice of grasping the planks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
204
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 200 publications
(216 citation statements)
references
References 92 publications
9
204
0
2
Order By: Relevance
“…For example, Loehr et al (2013) showed that pianists playing chords together distinguish errors which affect a pianist's own part only from errors which affect the harmony of the chord and so result in failure to achieve a collective goal. Richardson, Marsh, and Baron (2007) showed that acting together with another rather than alone can modulate how an individual grasps an object. And Novembre, Ticini, Schutz-Bosbach, and Keller (2013) showed that momentarily disrupting motor processes by means of double-pulse transcranial magnetic stimulation impairs a pianist's ability to appropriately adjust tempo to match her (recorded) partner's performance independently of impairing other aspects of her performance.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Loehr et al (2013) showed that pianists playing chords together distinguish errors which affect a pianist's own part only from errors which affect the harmony of the chord and so result in failure to achieve a collective goal. Richardson, Marsh, and Baron (2007) showed that acting together with another rather than alone can modulate how an individual grasps an object. And Novembre, Ticini, Schutz-Bosbach, and Keller (2013) showed that momentarily disrupting motor processes by means of double-pulse transcranial magnetic stimulation impairs a pianist's ability to appropriately adjust tempo to match her (recorded) partner's performance independently of impairing other aspects of her performance.…”
Section: Discussionmentioning
confidence: 99%
“…The perception of common or joint affordances may also be one process through which emergent coordination can be achieved (Richardson et al, 2007a). For instance, if it starts…”
Section: Joint Actions: Coordination Requirements and How To Meet Themmentioning
confidence: 99%
“…We agree with Smeets and Brenner (1999) that the distinction between intrinsic and extrinsic object properties is problematic. Not only can we think of properties that are hard to classify as either intrinsic or extrinsic (Smeets and Brenner mentioned object orientation), but also another literature (in the tradition of, so-called, aVordance research; see Gibson 1979;Warren 1984;Warren and Whang 1987) suggests that for the person wishing to pick up an object its size per se is not the relevant variable, but more so its size in relation to relevant body metrics (e.g., Newell 1999, 2000a, b;Van der Kamp et al 1998;Newell et al 1989;Richardson et al, 2007). For instance, the transition for picking up an object with a two or three-Wnger grip happens at the same ratio of object size and hand width for small children and adults, such that this transition happens at other object sizes for persons with diVerently sized hands (Newell et al 1989).…”
Section: Conditionmentioning
confidence: 99%
“…For instance, the transition for picking up an object with a two or three-Wnger grip happens at the same ratio of object size and hand width for small children and adults, such that this transition happens at other object sizes for persons with diVerently sized hands (Newell et al 1989). Interestingly, when faced with a series of objects of monotonically changing size, people change their behavior from grasping with one hand to grasping with two hands, even to grasping with two persons, at the same body-scaled size ratio (Richardson et al, 2007). From this perspective, one can impossibly speak of object size to be an intrinsic property.…”
Section: Conditionmentioning
confidence: 99%